Changes through Time in Tourism and Recreational Functions: A Case Study of Sokolniki - Makowska-Iskierka, Marzena (Turyzm/Tourism, 2004)
The article presents five aspects of change in the tourism and recreational functions of the garden- settlement of Sokolniki between 1987 and 2001. The analysis shows that Sokolniki can be classified as an urbanized tourism area, which represents the final stage of spatial transformation.